Study protocol for a pre/post study on knowledge, attitudes and behaviors regarding STIs and in particular HPV among Italian adolescents, teachers, and parents in secondary schools - Brunelli, Laura; Valent, Francesca; Comar, Manola; Suligoi, Barbara; Salfa, Maria Cristina; Gianfrilli, Daniele; Sesti, Franz; Restivo, Vincenzo; Casuccio, Alessandra; , ESPRIT Study Collaboration Group; Gazzetta, Silvia; Driul, Lorenza; et al. (Frontiers in Public Health, 2024)
Sexually transmitted infections (STIs) are one of the most important issues related to sexual and reproductive health, as it is estimated that more than 1 million new infections are acquired every day worldwide and data on the prevalence and incidence of these infections, especially among young people, are increasing. Nevertheless, there are some knowledge and behavioural gaps, and young people need more support from their school and family network to protect themselves and their peers. Therefore, we have designed a multicenter prospective intervention study involving public lower and upper secondary school students, their parents and teachers (ESPRIT). The intervention will take place in the school year 2023-2024, where students will meet with experts and be involved in peer education, while adults (parents and teachers) will participate in distance and face-to-face trainings. All target groups will complete KAP (knowledge, attitudes, practice) questionnaires before and after participating in the intervention to measure its effectiveness. The results of this study will help to assess and improve the level of knowledge of lower and upper secondary school students, parents and teachers about STIs Codice campo modificato and HPV in particular,; to raise awareness of sexual and reproductive health issues, including vaccination, among lower and upper secondary school students and their families, and evaluate the effectiveness of these interventions in terms of improving knowledge and changing attitudes and behaviours. The study protocol was has been approved by the Regional Unique Ethics Committee of Friuli Venezia Giulia (CEUR-2023-Sper-34). The project will is being carried out with the technical and financial support of the Ministry of Health -CCM.